Letter to the editor: vaccination against upper respiratory infections is a matter of survival in alcoholic liver disease$ppostscript : letters - Itzel, Timo; Falconer, Thomas; Daza Barragán, Jimmy Andres; Roig, Ana; Park, Jimyung; Cheong, Jae Youn; Park, Rae Woong; Wiest, Isabella; Ebert, Matthias; Hripcsak, George; Teufel, Andreas (Gut, 2023)
We read with great interest the report on SARS-CoV-2 infection in patients with primary biliary cholangitis (PBC) by Ampuero et al .1 An independent association of chronic liver disease with adverse clinical outcome in patients with COVID-19 was previously reported in this journal.2 However, the impact of SARS-CoV-2 and upper airway infections in general on patients with alcoholic liver disease (ALD) remains widely unknown. Yet, those data would be of high relevance to global public health and vaccination campaigns since alcohol related diseases are endemic. 57% of the population over age 15 has consumed alcohol in the last 12 months, and 2.3 billion people are current drinkers.3 - - With respect to upper airway respiratory infections, patients with chronic liver disease, including those with ALD, are particularly susceptible to infections as the immune system is dysfunctional through several pathological mechanisms including decreased opsonisation, reticuloendothelial dysfunction, neutrophils impairment and abnormal immunoglobulin synthesis.4 5 Moreover, alcohol abuse, independently from other factors, depresses the immune system by decreasing the lymphocytes and antibodies and the production of cytokines as TNF-alpha, IL-1 and IL-6.6 Several human and murine studies …
Gesehen am 01.07.2024